جدید نسائی افکار ونظریات کے معاصر عائلی نظام پر اثرات (شریعت اسلامیہ کے تناظر میں مسلم سماج کا مطالعہ): EFFECTS OF MODERN FEMINIST THOUGHTS AND IDEOLOGIES ON THE MUSLIM FAMILY SYSTEM (STUDY OF MUSLIM SOCIETY IN THE CONTEXT OF ISLAMIC SHARIA) - Dr Irfan Jafar; Hafiz Muhammad Usman; Mohsan Hassan (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
The Holy Qur’an delineates guidelines governing various aspects of human existence, particularly within personal and familial realms. As Islam is illuminated by the teachings of the Qur’an and the practices of the Prophet Muhammad ﷺ, it offers comprehensive directives on matters like marriage, divorce, adoption, pilgrimage, dowry, upkeep, inheritance, testamentary matters, polygamy, and the rights and obligations of spouses. It’s evident that the West has propagated a culture saturated with nudity and indecency under false banners of feminism and gender equality. This culture has become a significant burden for them today. European culture and family legislation have given rise to profound challenges for both America and Europe, leaving even the most eminent thinkers and intellectuals in these regions unable to find remedies. Their family structures are crumbling, and the core foundations of familial unity are disintegrating. Concurrently, contemporary feminist ideologies are observed to be promoting similar concepts within the Islamic context. Given these circumstances, it’s imperative for adherents of the true faith to courageously and wisely present Islam’s compassionate system to the world. They must clarify unequivocally that the inhumane civilization of Europe and its imposition of unnatural family laws have led the world to the brink of destruction. The sole path to salvation from this predicament lies in adhering to Islamic teachings and laws. In contemporary times, intellectually inclined women are actively working to reconcile Islamic teachings with modern principles. Notable figures in this movement include Amina Wadud, Asra Nomani, Ghazala Anwar, Shireen Khan, and Arshad Manji. Amina Wadud, in particular, is widely recognized as one of the first Muslim women in today’s world to lead mixed-gender congregational prayers in America. However, despite her groundbreaking actions, her book "Quran and Woman" only superficially touches upon this topic, lacking in-depth discussions on women leading congregational prayers, which remains a pertinent issue today. In the article under review entitled "Effects of Modern Feminist Thoughts and Ideologies on the Muslim Family System (Study of Muslim Society in the Context of Islamic Sharia)" family problems are described and their solution is presented in the light of Islamic Sharia.